2000
DOI: 10.1054/bjoc.2000.1502
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the tumour marker Cyfra 21-1 in carcinoma of head and neck and its role in early detection of recurrent disease

Abstract: Summary This study examines a new tumour marker, Cyfra 21-1, as a prognostic marker in predicting the survival of H&N cancer patients, and its correlation with clinical outcome during prolonged follow up of these patients. The study included 67 patients with primary detection of carcinoma of H&N. The survival of these patients was evaluated in correlation with the disease stage and Cyfra 21-1 levels at initial diagnosis. 38 patients were followed clinically and with serial assays for at least 12 months, or unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
1
33
1
1
Order By: Relevance
“…Previous studies have validated CYFRA 21-1 as a marker for monitoring disease in patients with various cancers, especially since CYFRA 21-1 concentrations and the sensitivity of CYFRA 21-1 increased progressively with clinical stage (Pujol et al, 1993;Sugama et al, 1994;Gaarenstroom et al, 1995;Takada et al, 1995;van der Gaast et al, 1995;Lai et al, 1996;Nakata et al, 1996;Brechot et al, 1997;Nisman et al, 1998;Brockmann et al, 2000;Doweck et al, 2000;Kawaguchi et al, 2000;Nakata et al, 2000) Our study also demonstrated that serum CYFRA 21-1 concentration was related to tumour stage of ICC, while serum CEA and CA 19-9 concentrations were not. CYFRA 21-1 concentrations differed according to the tumour size and vascular invasion, but not according to the number of tumours or nodal status.…”
Section: Cyfra 21-1 and Pathologic Variables In Patients With Iccmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have validated CYFRA 21-1 as a marker for monitoring disease in patients with various cancers, especially since CYFRA 21-1 concentrations and the sensitivity of CYFRA 21-1 increased progressively with clinical stage (Pujol et al, 1993;Sugama et al, 1994;Gaarenstroom et al, 1995;Takada et al, 1995;van der Gaast et al, 1995;Lai et al, 1996;Nakata et al, 1996;Brechot et al, 1997;Nisman et al, 1998;Brockmann et al, 2000;Doweck et al, 2000;Kawaguchi et al, 2000;Nakata et al, 2000) Our study also demonstrated that serum CYFRA 21-1 concentration was related to tumour stage of ICC, while serum CEA and CA 19-9 concentrations were not. CYFRA 21-1 concentrations differed according to the tumour size and vascular invasion, but not according to the number of tumours or nodal status.…”
Section: Cyfra 21-1 and Pathologic Variables In Patients With Iccmentioning
confidence: 99%
“…In non-small-cell lung cancer, CYFRA 21-1 was found to be significantly more sensitive than established markers, and this test may be a useful adjunct in clinical monitoring during and following treatment (Pujol et al, 1993;Stieber et al, 1993;Sugama et al, 1994;van der Gaast et al, 1994;Takada et al, 1995;Lai et al, 1996;Brechot et al, 1997;Nisman et al, 1998). In addition to lung cancer, CYFRA 21-1 has been reported to be a useful marker for cervical carcinoma (Gaarenstroom et al, 1995;Doweck et al, 2000), oesophageal cancer (Brockmann et al, 2000;Kawaguchi et al, 2000), breast cancer (Nakata et al, 2000), gastric cancer (Nakata et al, 1996), and bladder cancer - (Sanchez-Carbayo et al, 1999). Little is known, however, about the clinical significance of serum CYFRA 21-1 in primary liver cancer, although Kashihara et al (1998) have reported marked high concentration of serum CYFRA 21-1 in four patients with severe advanced ICC.…”
mentioning
confidence: 99%
“…The data including our study have shown that CYFRA 21-1 is a good marker for monitoring therapeutic effect, follow-up and prognostic value in patients with HNSCC. [2][3][4][5] Furthermore, many studies have shown that CYFRA 21-1 is useful for diagnosis of HNSCC. [5][6][7][8][9][10] We also believe that CYFRA 21-1 is an adjunct for the diagnosis of HNSCC.…”
Section: Elecsys 2010 Cyfra 21-1 Assaymentioning
confidence: 99%
“…2 It also mentioned an earlier study that demonstrated the persistence of small amounts of allergenic protein in peanut oil despite re nement. 3 Although the Committee on Safety of Medicines has determined that there is insuf cient evidence to conclude that exposure to topical medicines containletters to the editors…”
Section: Elecsys 2010 Cyfra 21-1 Assaymentioning
confidence: 99%
“…O mais acurado dado prognóstico para recidiva, no Entre os vários potenciais marcadores estudados, podem-se citar: expressão de moléculas de adesão caderina-E, CD44s, CD44v6 (13) ; a expressão de p53, EGFR, TGF-alfa e ciclina D1 (em carcinoma verrucoso, hiperplasia verrucosa e carcinoma epidermóide da região de cabeça e pescoço) (14) ; expressão do transportador-1 de glicose (em pacientes com carcinoma de hipofaringe) (15) ; p53 e ciclina D1(em CEC de laringe) (16) , dentre outros (17) . (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) . Destas, a osteopontina (OPN) parece ser o marcador mais promissor.…”
Section: Introductionunclassified